2020
DOI: 10.1016/j.jaci.2020.02.021
|View full text |Cite|
|
Sign up to set email alerts
|

Cutaneous barrier dysfunction in allergic diseases

Abstract: The fundamental defect(s) that drives atopic dermatitis (AD) remains controversial. ''Outside in'' proponents point to the important association of filaggrin gene mutations and other skin barrier defects with AD. The ''inside out'' proponents derive support from evidence that AD occurs in genetic animal models with overexpression of type 2 immune pathways in their skin, and humans with gain-of-function mutations in their type 2 response develop severe AD. The observation that therapeutic biologics, targeting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 139 publications
6
112
1
2
Order By: Relevance
“…Alteration to this lipid structure results in compromised epidermal functions and skin diseases such as atopic dermatitis. A strong skin barrier is required to prevent the penetration of microbes, allergens and irritants, and the subsequent activation of type-2 immune and inflammatory responses [ 105 ]. Clinical observations have concluded that skin lipid metabolism is critical in atopic dermatitis independent of the filaggrin genotype [ 105 ].…”
Section: Role Of Milk Fat and Mfgm In Infant Nutrition Growth Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Alteration to this lipid structure results in compromised epidermal functions and skin diseases such as atopic dermatitis. A strong skin barrier is required to prevent the penetration of microbes, allergens and irritants, and the subsequent activation of type-2 immune and inflammatory responses [ 105 ]. Clinical observations have concluded that skin lipid metabolism is critical in atopic dermatitis independent of the filaggrin genotype [ 105 ].…”
Section: Role Of Milk Fat and Mfgm In Infant Nutrition Growth Andmentioning
confidence: 99%
“…A strong skin barrier is required to prevent the penetration of microbes, allergens and irritants, and the subsequent activation of type-2 immune and inflammatory responses [ 105 ]. Clinical observations have concluded that skin lipid metabolism is critical in atopic dermatitis independent of the filaggrin genotype [ 105 ]. Skin lipids are critical for skin barrier integrity but also as antimicrobial and anti-inflammatory agents.…”
Section: Role Of Milk Fat and Mfgm In Infant Nutrition Growth Andmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] The pathogenesis of AD is complex and multifactorial explained by two complementary hypotheses: (a) inside out, the immune system defect drives the skin damage, and (b) outside in, in which the skin barrier defect drives the aberrant immune response. [1,5] In either case, there is an active cross talk between skin barrier and immune system; thus feeding a vicious cycle that supports the chronicity of the disease and the need to target both the skin barrier and the immune system to ensure optimal treatment of the disease.…”
Section: Backg Rou N Dmentioning
confidence: 99%